Computational modeling of the kinetics of lipase catalyzed reaction - Dabulyt-Bagdonavičienė, Jurgita; Ivanauskas, Feliksas; Razumas , Valdemaras (Lietuvos matematikos rinkinys, 2009)
The kinetics of lipase catalyzed reaction (hydrolysisof ascorbic acid palmitate), described by the system of simple non-linear differential equations was presented. The system was solved analytically and the result expressed by formula. With reference to calculated solution the current dependence on various parameters was performed. The comparison of experiments [3] and calculated results was made.
Keywords: computer simulation; kinetics of enzyme reaction; lipase